The development of the geographical thought starting from the work integrated with principles of the Geography in the Cuban school - Moreno-Henández, Mikel (2021)
The work proposes a rehearsal that bases the necessity to develop the geographical thought in the school context considering the possibilities of the principles of the geography. Different approaches are analyzed regarding the geographical thought and the features that this he/she should have to guide educational proposals in the teaching of the school Geography. Equally they stand out valuations to assume the principles of the geography like didactic axes in the teaching in the school, he/she allows to conform to a proposal that it integrates the localization principles, integrity, evolution and geographical scale in a structure that is composed of three stages with precise procedures to execute the educational work in the Cuban school. Starting from the contributed arguments you can conclude that the geographical thought has wide relevance in the process of geographical education in the basic high school and the principles of the geography can be a cardinal reference for its development.